UMPs Nur Khairiyah turns disappointment into joy, now works as engineer in Germany - T.N., Alagesh (MSN Sport, 2022)
KUANTAN: After passing her Sijil Pelajaran Malaysia (SPM) with flying colours in 2014, Nur Khairiyah Hibatullah Md Rosley secured a scholarship to pursue her dream of studying engineering in Germany.